Highly Anisotropic and Water Molecule-Dependent Proton Conductivity in a 2D Homochiral Copper(II) Metal–Organic Framework - Li, Rong; Wang, Shuai-Hua; Chen, Xu-Xing; Lu, Jian; Fu, Zhi-Hua; Li, Yan; Xu, Gang; Zheng, Fa-Kun; Guo, Guo-Cong (Chemistry of materials, 2017)
Proton conductivity research on single crystals is essential to elucidate their conduction mechanism and guide the unidirectional crystal growth to improve the performance of electrolyte materials. Herein, we report a highly anisotropic proton-conductive 2D metal–organic framework (MOF) [Cu2(Htzehp)2(4,4′-bipy)]·3H2O (1·3H 2 O, H3tzehp = N-[2-(1H-tetrazol-5-yl)ethyl]-l-hydroxyproline) with definite crystal structures showing single-crystal to single-crystal transformation between the anhydrate (1) and trihydrate (1·3H 2 O) phases. The hydrogen bonded chains consisted of well-defined lattice water molecules and hydroxyl functional groups of the Htzehp2– ligand array inside the 2D interlayer spaces along the crystallographic a-axis ([100] direction) in 1·3H 2 O. Temperature- and humidity-dependent proton conductivity was achieved along the [100] and [010] directions, respectively. The anisotropic proton conductivity of σ[100]/σ[010] in a single crystal of 1·3H 2 O was as high as 2 orders of magnitude. The highest proton conductivity of 1.43 × 10–3 S cm–1 of 1·3H 2 O at 80 °C and 95% relative humidity was observed among the reported 2D MOF crystals. The relation between the proton conductivity and structure was also revealed. The hydrogen bonded chain in 1·nH 2 O plays a significant role in the proton transport. The time-dependent proton conductivity and single-crystal X-ray diffraction measurements demonstrated that 1·3H 2 O is temperature- and humidity-stable and acts as an underlying electrolyte material for fuel cell applications.